1994
DOI: 10.1161/01.cir.89.5.2308
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilator responses of coronary resistance arteries of exercise-trained pigs.

Abstract: These results suggest that exercise training enhances bradykinin-induced vasodilation through increased endothelium-derived relaxing factor/nitric oxide production by the L-arginine/nitric oxide synthase pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
120
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 21 publications
21
120
0
1
Order By: Relevance
“…EX animals entered a progressive treadmill running program for 16 weeks, and SED animals remained inactive by cage confinement during this period. The exercise program has been used extensively by Laughlin and colleagues 7,8,16,17 and is similar to that described by Tipton et al 18 In brief, during the first week of training, animals ran at 4 to 5 mph, 0% grade for 15 minutes (sprint) and 3 mph, 0% grade for 20 to 30 minutes (endurance). Speed and duration were progressively increased depending on the ability of the animal.…”
Section: Exercise-training Programmentioning
confidence: 99%
See 2 more Smart Citations
“…EX animals entered a progressive treadmill running program for 16 weeks, and SED animals remained inactive by cage confinement during this period. The exercise program has been used extensively by Laughlin and colleagues 7,8,16,17 and is similar to that described by Tipton et al 18 In brief, during the first week of training, animals ran at 4 to 5 mph, 0% grade for 15 minutes (sprint) and 3 mph, 0% grade for 20 to 30 minutes (endurance). Speed and duration were progressively increased depending on the ability of the animal.…”
Section: Exercise-training Programmentioning
confidence: 99%
“…From each EX and SED animal, we isolated size-matched arterioles (Ϸ100 m ID) from both the collateral-dependent LCx region (distal to occlusion) and the nonoccluded LAD region; collateral-dependent arterioles were easily identified as arteriolar branches arising from LCx branch arteries distal to occlusion. Arterioles were evaluated as reported by Muller et al 8 Briefly, arterioles were placed into a Plexiglas chamber filled with Krebs solution (95% O 2 /5% CO 2 ; pH 7.4) and maintained at 4°C. Each end of the arteriole was cannulated with a glass micropipette (40-to 60-m ID) and secured with 10-0 Ethicon nylon suture.…”
Section: Isolation and Preparation Of Coronary Arteriolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelium dysfunction, which can be evidenced by an impairment in endothelium-dependent relaxation, plays a pivotal role in the pathogenesis of cardiovascular diseases, such as arterial hypertension and coronary heart disease (54), as well as in diabetic angiopathy (13). Moreover, NO interferes with key events involved in the development of atherosclerosis, such as smooth muscle cell proliferation, platelet adhesion and vessel wall interaction, and monocyte and leucocyte adhesion (54).Several studies demonstrated that chronic aerobic exercise alters endothelial function, improving vasodilating mechanisms mediated by NO (15,38,59), EDHF (33,36), and prostanoid metabolites (21), mainly in resistance vessels of the cardiac and skeletal muscle vascular beds (36,47). It is suggested that increased vascular wall shear stress associated with acute bouts of aerobic exercise may represent the main stimulus for vascular adaptations induced by chronic aerobic exercise (3,39,41).…”
mentioning
confidence: 99%
“…Several studies demonstrated that chronic aerobic exercise alters endothelial function, improving vasodilating mechanisms mediated by NO (15,38,59), EDHF (33,36), and prostanoid metabolites (21), mainly in resistance vessels of the cardiac and skeletal muscle vascular beds (36,47). It is suggested that increased vascular wall shear stress associated with acute bouts of aerobic exercise may represent the main stimulus for vascular adaptations induced by chronic aerobic exercise (3,39,41).…”
mentioning
confidence: 99%